2010
DOI: 10.2165/11536200-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Pharmacokinetics and Pharmacodynamics of Pregabalin and Gabapentin

Abstract: Pregabalin and gabapentin share a similar mechanism of action, inhibiting calcium influx and subsequent release of excitatory neurotransmitters; however, the compounds differ in their pharmacokinetic and pharmacodynamic characteristics. Gabapentin is absorbed slowly after oral administration, with maximum plasma concentrations attained within 3-4 hours. Orally administered gabapentin exhibits saturable absorption--a nonlinear (zero-order) process--making its pharmacokinetics less predictable. Plasma concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
411
3
25

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(443 citation statements)
references
References 37 publications
4
411
3
25
Order By: Relevance
“…This may be considered an observation that is in apparent contrast with gabapentinoids, similar to benzodiazepines, being GABA analogues only [26]. With a relatively short half-life of about 6 h, gabapentinoids are mostly ([98 %) excreted unchanged in the urine [15], with a urine specimen being positive for pregabalin for up to 5-6 days after intake in subjects with normal renal function [2].…”
Section: Methods/literature Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This may be considered an observation that is in apparent contrast with gabapentinoids, similar to benzodiazepines, being GABA analogues only [26]. With a relatively short half-life of about 6 h, gabapentinoids are mostly ([98 %) excreted unchanged in the urine [15], with a urine specimen being positive for pregabalin for up to 5-6 days after intake in subjects with normal renal function [2].…”
Section: Methods/literature Search Strategymentioning
confidence: 99%
“…Furthermore, orally administered pregabalin is absorbed more rapidly than gabapentin, with maximum plasma concentrations attained within 1 h as opposed to 3-4 h [15]. Indeed, the absolute bioavailability of gabapentin drops from 60 to 33 % as the dosage increases from 900 to 3,600 mg/day, while the absolute bioavailability of pregabalin remains at C90 % irrespective of the dosage [15].…”
Section: Pregabalin Vs Gabapentinmentioning
confidence: 99%
“…14 These drugs are only available for oral administration and the absorption of gabapentin is slow and limited by active transport in the gastrointestinal tract. 15,16 Plasma concentrations of gabapentin do not increase proportionally with increasing dose (non-linear absorption). In contrast, pregabalin absorption is more rapid and without a ceiling of amount absorbed.…”
Section: 6mentioning
confidence: 99%
“…Although, initial studies suggested that gabapentin may be effective in the treatment of migraine, it has since been shown to have only nominal potency in migraineurs (19). Pregabalin (Lyrica) displays more linear kinetics and a longer half-life than gabapentin (20) and has shown initially encouraging results as a potential treatment for migraine Significance Spreading depression is proposed to underlie migraine with aura, a type of debilitating headache for which few pharmacological treatments are available. The pain drug pregabalin has demonstrated initial promising results for the treatment of migraine in the clinic.…”
mentioning
confidence: 99%